Determinants of Implanon discontinuation among women who use Implanon at Debre Berhan town public health institutions in Northeast Ethiopia: a case–control study - Chekole, Moges Sisay; Zikie, Delelegn Tsegaye; Wogie Fitie, Girma; Taye, Birhan Tsegaw; Kibiret, Desta Mekete; Silesh Zerihun, Mulualem; Moltot Kitaw, Tebabere; Ali, Mohamed Ahmed; Legasu, Temesegen Desalegn; Assefa, Kibir Temesgen; Lemma Demisse, Tesfanesh (Frontiers in Global Women's Health, 2023)
Background Discontinuation of the most effective methods of contraception such as Implanon has now become a worldwide problem, which is significantly associated with mistimed and unwanted pregnancies and unsafe abortion, leading to an increased risk of maternal and child mortality and morbidity. However, studies on factors associated with Implanon discontinuation in Ethiopia, particularly in the area under this study, are limited. Therefore, this study aims to identify the determinants of Implanon discontinuation among women who used Implanon at Debre Berhan town public health institutions. Methods and materials A facility-based unmatched case–control study was conducted among 312 study participants (78 cases and 234 controls) from February 1, 2021, to April 30, 2021. The study participants were selected by using a systematic random sampling method for controls, and cases were selected consecutively until the required sample size was reached, during the data collection period. The data were collected by using a structured face-to-face interviewer-administered questionnaire and entered into Epidata version 4.6 and transferred to SPSS version 25 for analysis. Variables with a p-value of <0.25 in the bivariable analysis were entered into the multivariable logistic regression model. In the final model variables, a p-value of <0.05 was considered statistically significant at a 95% confidence interval (CI) and the strength of association was measured using an adjusted odds ratio (AOR). Results In this study, the determinants of Implanon discontinuation were the following: women who had no formal education (AOR: 3.57; 95% CI, 1.62–7.87), who had no children (AOR: 2.8; 95% CI, 1.50–5.17), who had no counseling about side effects (AOR: 2.43;95% CI, 1.30–4.55), who had no discussion with their partner (AOR: 2.7; 95% CI, 1.34–5.46), who had no follow-up appointment (AOR:2.81; 95% CI, 1.54–5.12), and who had side effects (AOR:1.91; 95% CI, 1.13–3.53). Conclusion and Recommendations Women's educational status, having no children during the insertion of Implanon, received no counseling about the side effects of insertion, no follow-up appointment, experiencing side effects, and no discussion with a partner were determinants of Implanon discontinuation. Hence, healthcare providers and other health sector stakeholders should provide and strengthen pre-insertion counseling, and follow-up appointments to increase the retention rates of Implanon.